2022
DOI: 10.1097/hnp.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Distant Reiki Sessions on Holistic Well-Being

Abstract: This study investigated the effect of distant Reiki sessions on the holistic well-being of people without no acute/chronic diseases. The study was conducted between February 1 and March 31, 2022. The sample consisted of 180 healthy people living in a city in Turkey. Participants attended 20-minute distant Reiki sessions (intervention) for 4 consecutive days. Pretest data were collected using a personal information form, the Holistic Well-Being Scale (HWBS), the Positive and Negative Affect Schedule (PANAS), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These study results also showed that Reiki positively affects quality of life by improving physical functioning, role limitations because of physical health problems, energy/fatigue, and emotional well-being (Shirani et al, 2019). Yüce et al (2024) conducted distance Reiki sessions for individuals without acute or chronic diseases for four consecutive days. They found that distance Reiki increased individuals' physical resistance, positively affected their psychosocial well-being, and improved their holistic well-being.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These study results also showed that Reiki positively affects quality of life by improving physical functioning, role limitations because of physical health problems, energy/fatigue, and emotional well-being (Shirani et al, 2019). Yüce et al (2024) conducted distance Reiki sessions for individuals without acute or chronic diseases for four consecutive days. They found that distance Reiki increased individuals' physical resistance, positively affected their psychosocial well-being, and improved their holistic well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Yüce et al (2024) conducted distance Reiki sessions for individuals without acute or chronic diseases for four consecutive days. They found that distance Reiki increased individuals' physical resistance, positively affected their psychosocial well-being, and improved their holistic well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations